DEFISIT ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN/KOTA PROVINSI DI SUMATERA SELATAN - Muhammad Bahrul Ulum; Ayu Geby Gisela Syaputri (MBIA, 2021)
This study aims to see how far the influence of regional own income, capital expenditure, and GDP on the budget deficit of regional own income and local expenditure in 14 districts/cities in South Sumatra province with used panel data with the number of time series from 2010-2019 and analysis method used is panel data regression by using fixed-effect model (FEM). The results of this study are regional own income and local expenditure have a positive effect on the increase in the budget deficit and GDP has a negative effect on the budget deficit in the South Sumatra province, and the magnitude of the influence of variables regional own income, local expenditure, and GDP with the budget deficit has a coefficient of determination of 94.3 percent which means that the variation of these variables in determining the budget deficit is very strong. Keywords: Budget Deficit, PAD, capital expenditure, GDP Abstak Penelitian ini bertujuan untuk melihat sejauh mana pengaruh pendapatan asli daerah, belanja modal dan PDRB terhadap Defisit Anggaran Pendapatan dan Belanja Daerah pada 14 kabupaten/kota di provinsi Sumatera Selatan dengan data yang digunakan adalah data panel dengan jumlah “time series” dari tahun 2010-2019 dan metode analisis yang digunakan adalah regresi data panel dengan menggunakan fixed effect model (FEM). Hasil dari penelitian ini adalah pendapatan asli daerah dan belanja modal memiliki pengaruh yang positif terhadap peningkatan defisit anggaran serta PDRB memiliki pengaruh yang negatif terhadap defisit anggaran di provinsi Sumatera Selatan, serta besaran pengaruh variabel pendapatan asli daerah, belanja modal dan PDRB terhadap defisit anggaran memiliki koefisien determinasi sebesar 94,3 persen yang berarti bahwa variasi variabel ini dalam menentukan defisit anggaran sangat kuat. Kata kunci: Defisit Anggaran, PAD, Belanja Modal, PDRB